Meningkatkan Ekonomi Kreatif Penduduk Miskin Melalui Pengembangan Kualitas Sumber Daya Manusia - Nursiya Bito; Franky A. Oroh; Agusyarif Rezka Nuha (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2023)
One aspect of success in implementing regional development is the achievement of human resource quality development. This is the concern of us as academics to play a role in realizing this aspect of success through community service activities. The implementation of community service activities is realized in the form of Thematic Community Service Program to optimize the potential and quality of human resources in Alale Village. The location is selectedÂ  because the local community is still not optimal in utilizing agricultural and plantation products. In addition, Alale Village is also a flood-prone area that requires more attention. The results of the activity show that people in this area are increasingly aware of the importance of developing traditional culinary products to realize Alale Village as a tourist village. This awareness can be seen by the increasing types of traditional culinary products sold in the village. In addition, the local people also understand the method or implementation of evacuation in the event of an emergency, such as flooding.